2022
DOI: 10.1111/jgh.15781
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of a serum glycome analysis in patients with colorectal cancer

Abstract: Background and Aim: Serum glycans are known to be good markers for the early diagnosis and prognostic prediction in many cancers. The aims of this study were to reveal the serum glycan changes comprehensively during the process of carcinogenesis from colorectal adenoma (CRA) to colorectal cancer (CRC) and to evaluate the usefulness of the glycan profiles as clinical markers for CRC. Methods: Serum samples were obtained from 80 histologically proven CRC and 36 CRA cases. The levels of glycans in the serum were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…The alteration of these eight significant N -glycans in CRC is displayed in Figure 2 , which shows a lower pre-operative expression of H4N4F1, H5N4F1, H5N4F1S 2,6 1, and H5N4F1S 2,3 2. These results are in line with previous reports that di-antennary structures with core fucosylation are decreased in CRC [ 14 , 25 , 26 , 27 ]. In addition, we also observed that H5N5F1 has a lower abundance in pre-operative CRC, which is supported by previous findings whereby bisected N -glycan species were also found to be decreased in serum as well as tissues from CRC patients [ 14 , 25 , 28 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The alteration of these eight significant N -glycans in CRC is displayed in Figure 2 , which shows a lower pre-operative expression of H4N4F1, H5N4F1, H5N4F1S 2,6 1, and H5N4F1S 2,3 2. These results are in line with previous reports that di-antennary structures with core fucosylation are decreased in CRC [ 14 , 25 , 26 , 27 ]. In addition, we also observed that H5N5F1 has a lower abundance in pre-operative CRC, which is supported by previous findings whereby bisected N -glycan species were also found to be decreased in serum as well as tissues from CRC patients [ 14 , 25 , 28 ].…”
Section: Resultssupporting
confidence: 93%
“…In relation to this, the isotopic profile of H6N5S 2,3 1S 2,6 2 (isomer 2) is shown in Supplementary Figure S1 . Takei et al analyzed the serum N -glycome using a previous iteration of the Bruker MALDI instrument, the ultraflex III, which resulted in the quantification of 34 N -glycans [ 25 ]. Thus, it is likely that the current workflow could be improved by coupling with a mass spectrometer with higher resolving power and greater sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…CRC is one of the most common malignant tumors of digestive system in clinical practice and ranks third in the incidence rate of cancer worldwide 12 . Over the past 30 years, the living standards of the people have been improving, and the diet structure has changed 13 .…”
Section: Discussionmentioning
confidence: 99%
“…CRC is one of the most common malignant tumors of digestive system in clinical practice and ranks third in the incidence rate of cancer worldwide. 12 Over the past 30 years, the living standards of the people have been improving, and the diet structure has changed. 13 Most countries including China have experienced an increasing incidence rate of CRC, which has seriously endangered people's health.…”
Section: Discussionmentioning
confidence: 99%
“…This was recently addressed in a study using ultra performance liquid chromatography and demonstrating distinct serum IgG N-glycan profiles for AA and CRC ( 92 ). Another group studying 34 serum glycans reported that 9 of both hybrid-type and multiantennary glycans were differentially expressed between CRC and AA ( 93 ). Not only glycosylated proteins but also glycan-binding proteins such as galectin-2, galectin-3, galectin-4, and galectin-8 are found to be elevated in the serum from patients with CRC.…”
Section: Aberrant Glycosylation During the Adenoma-to-carcinoma Sequencementioning
confidence: 99%